The metaphysics of evil of Markis de Sade, that is on the meaninglessness of Other - Mikołajczyk, Hubert T. (Folia Philosophica, 2008)
The author concentrates on the so called metaphysics of evil as a direct consequence of Nietzschean „God’s death”. Treating a libertinian philosophy of immorality as the focal point of a „wicked morality”, he proves that a „reverse interpretation of Plato” proposed by Markis de Sade, constitutes a rejection of both arche and telos of any morality. As a result, freedom of our action, without any moral objections, equals the negation of the Enlightenment reason tasks as the main perspective of „Thinking Nietzsche”. It turns out to be the moment in which transcendental attempts to build metaphysics beyond an unaware optics of sheer madness are regarded unjustified. Thus, it is not reason, but the achievements by Jacques Derrida and Michel Foucault in opposition to it and following the trace of considerations by de Sade that become a post Nietzschean canon of the contemporary „philosophy of the subject”.